Political Biography Of Vemavaram Manohar Pantulu: A Study - Venkat Reddy, Yandapally (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Before Indian Independence, Hyderabad state was a princely state within the territory of British India companised of three linguistic regions the Telugu speaking Telangana area (including the capital city Hyderabad), the marati speakingl Marathwada area and a small kannada speaking area. Telangana occupied 50 of the state’s area. The ruling elites including the Nizam were muslim, while the majority were Hindus. In the Telangana region of the Erst while in 1946-51. Hyderabad state was a pivotal movement in Indian history, because of its impact on the future of the communist in India and its higher lightning of the condition of the Indian peasantry. It brought the struggle of the present to the fore front and serve as a remainder of the sacrifice made by the people of this region in fighting against the auto-cratic rule of the Nizam of Hyderabad and the feudal regime that concentrated power and land in the hands of few. A large number of people participated in the popular struggle. The Nalgonda district played on significant role in the armed struggle. The prominent among them were Arutla Rama Chandra reddy, Arutla Kamala devi, Gurunath reddy, Bheemreddy Narasimha reddy, Mallu swarajyam and like Vemavaram Manohar panthulu also played key role in the Telangana armed struggle. An attempt is made in this paper to study the brief biographical sketch of Vemavaram Manohar panthulu and his contribution on to Telangana armed struggle.